2019
DOI: 10.1111/jfd.13069
|View full text |Cite
|
Sign up to set email alerts
|

First isolation of Flavobacterium psychrophilum associated with reports of moribund wild European eel (Anguilla anguilla) in Scotland

Abstract: In late April 2015, the River Dee Trust informed Marine Scotland Science, Fish Health Inspectorate (FHI), that there had been observations of dead and moribund European eels on the River Dee. Later in May, the Spey Fishery Board also reported a number of moribund European eels in a rotary screw smolt trap on the River Spey. In total, 10 cases involving moribund eels were investigated in 2015 and one case in 2016. In addition, a health screen was conducted to investigate the potential presence of Flavobacterium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Flavobacterium psychrophilum is one of the main bacterial pathogens causing significant economic losses in salmonid aquaculture worldwide and the range of fish species naturally affected by this bacterium has been increasing in recent years. Thus, the bacterium has also been isolated from non‐salmonid cultured species, producing a milder disease and suggesting a possible reservoir role for these hosts (Nematollahi et al, 2003; Soares et al, 2019). In this study, we describe the first isolation of F .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavobacterium psychrophilum is one of the main bacterial pathogens causing significant economic losses in salmonid aquaculture worldwide and the range of fish species naturally affected by this bacterium has been increasing in recent years. Thus, the bacterium has also been isolated from non‐salmonid cultured species, producing a milder disease and suggesting a possible reservoir role for these hosts (Nematollahi et al, 2003; Soares et al, 2019). In this study, we describe the first isolation of F .…”
Section: Discussionmentioning
confidence: 99%
“…Although salmonids, especially juvenile rainbow trout ( Oncorhynchus mykiss ) and coho salmon ( Oncorhynchus kisutch ), are particularly susceptible to the disease, infections of non‐salmonids have also been described. Thus, F. psychrophilum has also been reported in Japanese eel ( Anguilla japonica ), European eel ( Anguilla anguilla ), common carp ( Cyrpinus carpio ), crucian carp ( Carassius carassius and Carassius auratus langsdorfi ), tench ( Tinca tinca ), ayu ( Plecoglossus altivelis ), pale chub ( Zaco platypus ), perch ( Perca fluviatilis ), roach ( Rutilis rutilis ), Indian catfish ( Clarias batrachus ), lamprey ( Petromyzon marinus L.), gobies ( Chaenogobius urotaenia and Rhinogobius brumneus ) and Japanese dace ( Trybolodon hakonensis ) (Soares et al, 2019). Infections of non‐salmonid fish produce an apparently less severe disease compared to infected salmonids, suggesting a natural resistance and a possible reservoir role for these fish species (Nematollahi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…( A. hydrophila complex, A. sobria complex, and A. caviae complex, A. jandei ) [ 7 ], Pseudomonas anguilliseptica [ 8 ], Edwardsiella tarda [ 9 ] and Edwardisiella anguillarum [ 10 ]. Other bacteria, such as flavobacteria, are commonly responsible for necro-ulcerative skin lesions [ 11 ]. Diseases caused by cocci, such as fish streptococcosis, are frequent in other fish species but are rarely reported in eel [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among infectious diseases, bacterial diseases are the most common in farming. Studies have shown that muscle is one of the target organs of many bacterial infections in aquatic animals, showing pathological signs such as congestion, hemorrhage, and necrosis after infection ( Dong et al, 2017 ; Soares et al, 2019 ; Sun et al, 2020 ). In addition, reports on the nutritional loss of muscle caused by bacterial infections are also available ( Berney and Berney-Meyer, 2017 ).…”
Section: Introductionmentioning
confidence: 99%